PENGARUH FAKTOR LOKASI, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UMKM SUNTHAI TEA STABAT - Nisa, T. Chairatul; Siregar, Onan Marakali (Transpublika Publisher, 2022)
Consumer satisfaction is how consumers feel when comparing what they anticipated to what they really received. Maintaining customer satisfaction is crucial for both large and small organizations, including MSMEs, because a company can only survive and expand if it maintains and increases customer satisfaction. This study aims to determine how location, product and service quality, and location effect customer satisfaction in small and medium-sized enterprises (SMEs) such as Sunthai Tea Stabat. In this research, collaboration and a quantitative approach are employed. The research populations consists of those who buy sunthai tea product, and 100 of them were requested to complete a questionnaire. According to the research findings, location (X1) has a significant effect on consumer satisfaction. Meanwhile, product quality (X2) has a significant impact on customer satisfaction. In addition, service quality (X3) has a significant impact on customer satisfaction. However, location, product quality, and service quality all impact consumer satisfaction simultaneously. This study concludes that Sunthai Tea Stabat's location MSME, product quality, and service quality all have positive and statistically significant effects on consumer satisfaction.